Comparison of Muscle and Subcutaneous Tissue Fatty Acid Composition of Bangladeshi Nondescript Deshi Bulls Finished on Pasture Diet - Mohammad Khairul Alam; Ziaul Hasan Rana; Mohammad Akhtaruzzaman (Journal of Chemistry)
The objective of this study was to characterize and compare the tissue-associated differences in the fatty acid profiles of intramuscular and subcutaneous fat from pasture fed nondescript deshi breed bulls of Bangladesh. The average chemical composition of the longissimus muscle was as follows: moisture 74.65±0.48%, protein 21.55±0.83%, intramuscular fat 2.78±0.28%, and ash 1.02±0.03%. There was significant evidence that the lipids of longissimus muscle from the nondescript deshi bulls had a lower content of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and conjugated linoleic acid (CLA) and a higher content of polyunsaturated fatty acids (PUFA) compared to subcutaneous fat. Intramuscular fat also showed the highest PUFA/SFA and ∑n-6/∑n-3 fatty acids ratios and total n-3 and n-6 PUFAs compared to subcutaneous tissue depots. Overall findings suggest that the meat from pasture fed nondescript deshi breed can be considered as lean meat and healthy for human consumption.